Skeletal Remains from Three Ancient Slav Graves Excavated in the Courtyard of The Slovene Academy in Ljubljana - Škerlj, B. (Arheološki vestnik, 1950)
In 1948/49 several graves w ere found in the back-yard of the A cadem y of Sciences and A rts in L jubljana, belonging to th e seventh to eighth centu[1]ries A. D. as to the accessories (J. Korošec) being ancient Slav. O nly three skeletons, respectively th eir rem ains w ere capable of being treated anthropologically. K-1S is an about 25 years old, approxim ately 169 cm (as to th e hum erus) high, strong man, w ith w ell developed torus supraorbitales, Aith a w ell-pre[1]served su tu ra metopica, a wide, strong m andibula w hich is b roken in the space of P2 on account of its crow n having been placed below the roots of Mr The m andibula has in the gonions turned-out edges and a vigorous, wide pro tu b eran tia mentis. The teeth are healthy, b u t strongly w hetted-off. The orbitae are high, ra th e r quadrangular. It is of Crom agnon type. K-13 is an about 18 y ea r old woman, approxim ately only 150 cm high (as to the hum erus + radius). Lower, q u adrangular orbitae, a turned-out edge of an else much sm aller m andibula (beside other characters) are ap parently of Crom agnon type as well, w hich w as ra th e r frequent in ancient Slavs. The teeth are healthy, only the rig h t Mt is decaying, on the w hole th e Mi are rath e r w hetted-off. The bicristal w idth of the pelvis is 268 mm, diam eter transversus lineae arcu atae 120 mm, th e greatest w idth of the os sacrum 112 mm. In the right’ hum erus there is an interesting perforatio fossae ole[1]crani. The radio-hum eral index is 77,5, i. e. normal. K-9. A badly p reserved skeleton, very delicate, possibly of a 15 years old girl. In com paring these three skulls w ith the m aterial of Bled from 1948 there is nothing to be seen th a t m ight be essentially different. All other data are» to be seen in the table